2012
DOI: 10.1071/ah11082
|View full text |Cite
|
Sign up to set email alerts
|

International medical graduates' reflections on facilitators and barriers to undertaking the Australian Medical Council examination

Abstract: Objective. In Australia, 25% of international medical graduates (IMGs) make up the medical workforce. Concern is expressed in the literature about the lack of awareness and knowledge of issues that impinge on IMGs’ education. Although there is literature alluding to difficulties IMGs face with undertaking the Australian Medical Council (AMC) examination, there is little research detailing this experience. We therefore explored IMGs’ reflections on facilitators and barriers in undertaking the AMC examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Some IMGs reported that it was beneficial for them to take this exam in their country of origin, and they were able to pass the exam on their first attempt. IMGs have also highlighted the shortening of the examination process without enduring travelling expenses (McGrath, Henderson, Holewa, Henderson, Tamargo, 2012).…”
Section: Australian Medical Council (Amc) Examinationsmentioning
confidence: 99%
“…Some IMGs reported that it was beneficial for them to take this exam in their country of origin, and they were able to pass the exam on their first attempt. IMGs have also highlighted the shortening of the examination process without enduring travelling expenses (McGrath, Henderson, Holewa, Henderson, Tamargo, 2012).…”
Section: Australian Medical Council (Amc) Examinationsmentioning
confidence: 99%
“…15,16,20,36,39,46,[54][55][56]58,59,65,69,[72][73][74][75][76][77][78][79][80][81][82][83] An IMG who was a native of the host country but qualified in another country did not suffer culture shock in society compared with an IMG who immigrated from another country. 14,47,71,73 However, the former was likely to suffer a workplace culture shock, especially if the country of PMQ had a very different healthcare system and workplace culture. 68 The same principle applied to differences in medical education between country of PMQ and host countries.…”
Section: Degree Of Dissonancementioning
confidence: 99%
“…The four main barriers that IMGs faced appeared to be the differences in language, 18,36,37,40,42,46,[70][71][72] culture, 15,16,20,36,39,46,55,56,58,59,65,69,[72][73][74][75][76][77][78][79][80][81][82][83] medical education, 14,16,54,[75][76][77]80 and belonging. 15,19,20,35,46,54,55,57,59,68,72,81 It was the extent to which the IMGs' language,...…”
Section: Degree Of Dissonancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, while the sociopragmatic expectations in both Germany and Australia are that new employees or important visitors should be introduced, on a pragmalinguistic level German speakers might prefer formal introductions using multiple honorifics and surnames such as Herr/Frau/Doktor Schmidt, whereas Australians might introduce themselves more informally, giving their first name John/Jane and so forth (Clyne, 2006). Such aspects of communication can be particularly difficult for IMGs to understand and acquire as, in both Australia and Canada, communication and other kinds of support programs are often limited (McGrath, Henderson, Holewa, Henderson, & Tamargo, 2012), poorly integrated (Zulla, Baerlocher, & Verma, 2008), focused on systemic rather than communication issues (e.g., Lockyer, Fidler, de Gara, & Keefe, 2010), or inaccessible due to geographic isolation or financial constraints (Sommer, MacDonald, Bulsara, & Lim, 2012). Moreover, such micropragmatic features are frequently underrepresented in or entirely left out of the curriculum of both general and specialist communication programs, in part because a reliable context-relevant evidence base is still lacking (Derwing & Waugh, 2012;Yates, 2008).…”
Section: Introductionmentioning
confidence: 99%